Universidade, vestibulares e ideologia - Whitaker, Dulce C. A. [UNESP] (Universidade Estadual Paulista (Unesp), 1983)
As funções do exame vestibular à luz das necessidades políticas de diferentes moments históricos. Análise crítica das mudanças ocorridas nesse tipo de concurso a partir da consolidação do capital monopolista no Brasil, bem como do enrijecimento dessa barreira escolar face à crise do mercado de trabalho para formados em nível superior. A problemática do ensino superior pago como decorrência.

The functions of entrance examination under the light of the political needs of diferent historical moments. The critical analysis of changes which have occurred in such a type of exam from the consolidation of the monopolist capital in Brazil, as well as the herdening of such a school barrier due the labour market for university graduates. The problem of the paid university education as a consequence.
University, entrance examinations and ideology
Keywords: Ideologia e política educacional; Exame vestibular; Análise crítica; Ensino superior pago; Carreira de nível superior; Mercado de trabalho; Ideology and political education; Entrance examination; Critical analysis; Paid University education